Microstructural and Fractographic Analysis of Plastically Deformed Al-Zn-Mg Alloy Subjected to Combined High-Cycle Bending-Torsion Fatigue - Aleksander Kowalski; Wojciech Ozgowicz; Wojciech Jurczak; Adam Grajcar; Sonia Boczkal; Andrzej Kurek (Metals, 2018)
The present manuscript aims to determine the effect of various deformation levels during low-temperature thermo-mechanical treatment (LTTT) on the microstructure and fatigue strength of Zr-microalloyed Al-Zn-Mg alloy. The fatigue strength of the alloy was studied in high-cycle bending-torsion tests. The determination of the influence of plastic deformation level during LTTT on the microstructure was based on transmission electron microscopy (TEM) observations. The analysis of fracture after the fatigue tests was performed based on fractographic images using scanning electron microscopy (SEM). It was found that the major factor affecting the microstructure of the alloy, and determining the nature of fatigue fracture, is the strain level applied during LTTT.